2021
DOI: 10.1158/2159-8290.cd-21-0999
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Induces a Stress Ileopathy Depending on β-Adrenergic Receptors and Promoting Dysbiosis that Contributes to Carcinogenesis

Abstract: Gut dysbiosis has been associated with intestinal and extraintestinal malignancies, but whether and how carcinogenesis drives compositional shifts of the microbiome to its own benefit remains an open conundrum. Here, we show that malignant processes can cause ileal mucosa atrophy, with villous microvascular constriction associated with dominance of sympathetic over cholinergic signaling. The rapid onset of tumorigenesis induced a burst of REG3γ release by ileal cells, and transient epithelial barrier permeabil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 80 publications
1
34
0
Order By: Relevance
“…With the increasing research on the relationship between microbiota and systemic tumors (especially digestive tract tumors), many studies have reported that oral microbiota is related to colorectal cancer (CRC) ( Flemer et al., 2018 ; Zhang et al., 2020 ), esophageal cancer ( Chen et al., 2015 ), pancreatic cancer ( Farrell et al., 2012 ; Torres et al., 2015 ), and oral cancer ( Pushalkar et al., 2012 ; Schmidt et al., 2014 ), while fecal microbiota is related to CRC ( Flemer et al., 2017 ), liver cancer ( Ren et al., 2019 ), and breast cancer ( Terrisse et al., 2021 ). Due to microbial differences between tumor patients and healthy controls (HC), microbial detection has the potential to be a new non-invasive screen test ( Flemer et al., 2018 ; Ren et al., 2019 ; Zhang et al., 2020 ; Yonekura et al., 2021 ). In the meantime, the role of gastrointestinal (GI) microbiota in the oral cavity and stool in GC remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing research on the relationship between microbiota and systemic tumors (especially digestive tract tumors), many studies have reported that oral microbiota is related to colorectal cancer (CRC) ( Flemer et al., 2018 ; Zhang et al., 2020 ), esophageal cancer ( Chen et al., 2015 ), pancreatic cancer ( Farrell et al., 2012 ; Torres et al., 2015 ), and oral cancer ( Pushalkar et al., 2012 ; Schmidt et al., 2014 ), while fecal microbiota is related to CRC ( Flemer et al., 2017 ), liver cancer ( Ren et al., 2019 ), and breast cancer ( Terrisse et al., 2021 ). Due to microbial differences between tumor patients and healthy controls (HC), microbial detection has the potential to be a new non-invasive screen test ( Flemer et al., 2018 ; Ren et al., 2019 ; Zhang et al., 2020 ; Yonekura et al., 2021 ). In the meantime, the role of gastrointestinal (GI) microbiota in the oral cavity and stool in GC remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, emerging evidence indicates that carcinogenesis induces regenerating islet-derived protein 3 γ (Reg3-γ)-mediated β-adrenergic receptor-dependent epithelial permeability and, consequently, Clostridium spp.-dominant dysbiosis. This finding implicates the gut microbiota in carcinogenesis and cancer progression ( 25 ). Collectively, these data provide compelling preclinical evidence that gut microbiota mediate the efficacy of a range of anticancer therapies, including chemotherapy, radiotherapy, and immunotherapy.…”
Section: The Gut Microbiome In Cancer Immunotherapymentioning
confidence: 63%
“…In our study, we used a different antibiotic cocktail including ampicillin, streptomycin, and colistin without vancomycin. We have accumulated data to show that vancomycin depletes immunosuppressive bacteria such as Clostridia spp 65 , suggesting that this point is indeed crucial. Second, Pernigoni et al 56 performed surgical castration (which is rarely used in the treatment of human PC), while we used chemical castration with an LHRH antagonist (Degarelix).…”
Section: Discussionmentioning
confidence: 99%